Everyday Consumption in Twenty-First-Century Brazilian Fiction (Purdue University Press, 2022)
Everyday Consumption in Twenty-First-Century Brazilian Fiction is the first in-depth study to map out the representation of consumption in contemporary Brazilian prose, highlighting how our interactions with commodities connect seemingly disconnected areas of everyday life, such as eating habits, the growth of prosperity theology, and ideas of success and failure. It is also the first text to provide a pluralistic perspective on the representation of consumption in this fiction that moves beyond the concern with aesthetic judgment of culture based on binaries such as good/bad or elevated/degraded that have largely informed criticism on this body of literary work. Current Brazilian fiction provides a variety of perspectives from which to think about our daily interactions with commodities and about how consumption affects us all in subtle ways. Collectively, the narratives analyzed in the book present a wide spectrum of more or less hopeful portrayals of existence in consumer culture, from totalizing dystopia to transformative hope.